Dynamic characteristics of otolith ocular response during counter rotation about dual yaw axes in mice - Shimizu, Naoki (Neuroscience, 2014)
The central vestibular system plays an important role in higher neural functions such as self-motion perception and spatial orientation. Its ability to store head angular velocity is called velocity storage mechanism (VSM), which has been thoroughly investigated across a wide range of species. However, little is known about the mouse VSM, because the mouse lacks typical ocular responses such as optokinetic after nystagmus or a dominant time constant of vestibulo-ocular reflex for which the VSM is critical. Experiments were conducted to examine the otolith-driven eye movements related to the VSM and verify its characteristics in mice. We used a novel approach to generate a similar rotating vector as a traditional off-vertical axis rotation (OVAR) but with a larger resultant gravito-inertial force (>1 g) by using counter rotation centrifugation. Similar to results previously described in other animals during OVAR, two components of eye movements were induced, i.e. a sinusoidal modulatory eye movement (modulation component) on which a unidirectional nystagmaus (bias component) was superimposed. Each response is considered to derive from different mechanisms; modulations arise predominantly through linear vestibulo-ocular reflex, whereas for the bias, the VSM is responsible. Data indicate that the mouse also has a well-developed vestibular system through otoliths inputs, showing its highly conserved nature across mammalian species. On the other hand, to reach a plateau state of bias, a higher frequency rotation or a larger gravito-inertial force was considered to be necessary than other larger animals. Compared with modulation, the bias had a more variable profile, suggesting an inherent complexity of higher-order neural processes in the brain. Our data provides the basis for further study of the central vestibular system in mice, however, the underlying individual variability should be taken into consideration.